Computational Thinking Skills to Solve Kinematics Problems at High Cognitive Level Cases - Rabiudin; Erwinestri Hanidar Nur Afifi; Tiara Widya Hastuti; Dian Choiru Nisa (Jurnal Penelitian Pendidikan IPA, 2023)
Problems of kinematics of rectilinear motion in high-level cognitive level problems often display complexity in their solutions. This research aims to describe the use of computational thinking (CT) methods in helping students solve linear motion kinematics problems designed at a high cognitive level (analysis, evaluation, and creation). This research uses a descriptive quantitative method by using skills observation sheets and analysis of performance results as data collection instruments. The sample was 14 students from the Natural Sciences Tadris study program in introductory physics courses. This research's data analysis technique uses an interpretation of student performance results in solving linear motion kinematics questions at a high cognitive level using the performance stages of the CT method. Significant findings show that the average student cannot solve cases at a high cognitive level using CT skills. Students can only complete and pass the stages of computational thinking skills in the temporary decomposition and abstraction phases but have difficulties in the visualization and design stages at the analysis, evaluation, and creation levels.